دراسة تحليلية للنظام التربوي في جمهورية أفلاطون - موسى، محمد (جامعة البعث, 2013)
بالرغم من أن جمهورية أفلاطون مشهورة بالدفاعات القضائية الحاسمة حول العدالة، فهي أيضاً مسلحة بدفاع تعليمي فلسفي قوي. إن حجج وبراهين إيمان أفلاطون بالتربية كثيرة، ولكن من الصعوبة بمكان توضيحها وذلك بسبب تعقيدات الحوار الذي يستخدمه في كتابه الجمهورية. من جهة أخرى، لم يفرض سقراط (على لسان أفلاطون) رؤيتين (تفسيرين) مختلفتين للتربية فقط (الأولى هي تعليم أولياء الأمور والثانية هي تعليم الفلاسفة الملوك)، بل أيضاً بين الأهمية غير الملحوظة للتربية عبر الطرق التربوية التي استخدمها مع الشخصيتين (غلاكون -وأديمانتوس). \ سنحاول في هذا البحث دراسة الحوار من وجهة نظر كل من التفسيرين الواضحين للتربية، وسنحاول أن نبين التشابهات والاختلافات بينهما. وبعد تقديم تفسيراً وفهماً لكل منهما، سنحاول تحليلهما في ضوء منهج سقراط التربوي، وبهذا لنكشف القناع عن أفكار سقراط في التربية. Although Plato's Republic is best known for its definitive defense of justice, it also includes an equally powerful defense of philosophical education. Plato's beliefs on education, however, are difficult to discern because of the intricacies of the dialogue. Not only does Socrates (Plato's mouthpiece in the dialogue) posit two differing visions of education (the first is the education of the warrior guardians and the second is the philosopher-kings' education), but he also provides a more subtle account of education through the pedagogical method he uses with Glaucon and Adeimantus. While the dramatic context of the dialogue makes facets of the Republic difficult to grasp, in the case of education, it also provides the key to locating and understanding Socrates' true vision of education. \ Socrates' pedagogical approach with the interlocutors corresponds closely with his vision of the education of the philosopher-kings--an overlap which suggests that the allegory of the cave is representative of true Socratic education. \ This paper will first examine the dialogue's two explicit accounts of education, addressing both their similarities and differences. After gaining an understanding of the two accounts, the paper will analyze them in relation to Socrates' own pedagogical method, and thereby unveil the ideals of Socratic education.
Keywords: الفلسفة اليونانية -- الفلاسفة اليونانيون -- افلاطون -- كتاب الجمهورية -- النظام التربوي